2004
DOI: 10.1074/jbc.m400898200
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for ATP by the DNA Damage Checkpoint Clamp Loader

Abstract: The DNA damage clamp loader replication factor C (RFC-Rad24) consists of the Rad24 protein and the four small Rfc2-5 subunits of RFC. This complex loads the heterotrimeric DNA damage clamp consisting of Rad17, Mec3, and Ddc1 (Rad17/3/1) onto partial duplex DNA in an ATP-dependent manner. Interactions between the clamp loader and the clamp have been proposed to mirror those of the replication clamp loader RFC and the sliding clamp proliferating cell nuclear antigen (PCNA). In that system, three ATP molecules bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 28 publications
(59 reference statements)
1
36
0
Order By: Relevance
“…3A, loading of PCNA by Elg1-RFC was also not observed (data not shown). This complex also failed to load the DNA damage checkpoint clamp Rad17/Mec3/Ddc1 onto primed DNA, under conditions that gave efficient loading by Rad24-RFC, leaving it currently as the only clamp loader with no specific biochemical function (data not shown) (29).…”
Section: Resultsmentioning
confidence: 99%
“…3A, loading of PCNA by Elg1-RFC was also not observed (data not shown). This complex also failed to load the DNA damage checkpoint clamp Rad17/Mec3/Ddc1 onto primed DNA, under conditions that gave efficient loading by Rad24-RFC, leaving it currently as the only clamp loader with no specific biochemical function (data not shown) (29).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have shown that hRAD17-RFC as clamp loader recruits the 9-1-1 complex to the location of DSBs. 22,[32][33][34][35] Phosphorylation of hRAD17 by ATR upon DNA damage is necessary for the DNA damage checkpoint response. 31,36 Therefore, hRAD17 may be involved in DNA repair synthesis and mediate cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of hRAD17 expression occurs frequently in HNSCC, is often due to genomic deletion, and may facilitate genomic instability in HNSCC. V V C 2007 Wiley Periodicals, Inc. Head Neck 30: [35][36][37][38][39][40][41][42]2008 Keywords: head and neck cancer; LOH; chromosomal instability; downregulation; hrad17 Cells respond to DNA damage by activating a highly coordinated DNA damage response. Failure to monitor and to signal DNA damage leads to genomic instability, which can ultimately lead to cancer formation due to dysregulation of critical genes that maintain cellular homeostasis.…”
mentioning
confidence: 99%
“…Proteins, Yeast Strains, and DNA-The checkpoint factors and DNA polymerase ␦ (pol ␦) were overproduced in yeast and purified as described previously (12,15,16). PCNA and RFC (a version lacking the N-terminal 172-amino-acid domain of Rfc1) were overproduced in Escherichia coli (17).…”
Section: Methodsmentioning
confidence: 99%